Psychologists in training’s Assumption about Mind and Brain in Psychopathology and Clinical Work - Mavundla, Patricia Lungile (University of the Witwatersrand, Johannesburg, 2024)
Research Purpose: The study's objective was to understand how psychologists in training endorsed models of illnesses for mental disorders. The results aimed to understand how they differed in their levels of training, and the results for the theoretical orientations endorsed analysed the mean significance for both the clinical and counselling training groups. Methodology: The study was conducted using first-year master's clinical and counselling psychology students, and the total sample was N = 28. The study's population was drawn from six universities in South African and investigated using a quantitative research design. A survey was used to gather data from the participants, and the data was analysed using the IMB Statistical Package for the Social Sciences (SPSS) software version 27. An analysis of variance test (ANOVA) was used to analyse the data and four research questions compared how the level of endorsement differed across different models of mental disorders, determined any trends for the different levels of endorsement which differed depending on which training programs the participants received, it also determine whether the theoretical orientation of training receiving differed, and lastly determined whether the effects training received differed based on the individual psychotherapy the participants received. The research questions were used as the framework for the study, with four mental disorders used as items, eight models of illness used to analyse the theoretical orientations endorsed, and a Maudsley Attitude Questionnaire (MAQ) used as a measure for the items. Results: The results indicated a significant difference between the clinical and counselling groups. A line graph illustrated how the mental disorders were endorsed differently, and as a result, the level of endorsement for the social realist model of illness (M=15.28, SD=2.05) was highly endorsed, and the Nihilist model of illness (M=8.21, SD=2.69) was the least endorsed. Discussion: Participants from diverse institutions had an impact on how well they understood the different mental disorders and endorsed the models of illnesses. Considering that there was not enough data entry, there were a few deviations with the data collection and the results could not comply with a larger population of trainee psychologist. Conclusion: The outcome of this study aims contribute to research in academia in terms of understanding the factors that influence the choice of treating mental disorders and may help enhance psychologists’ choice of choosing the correct models of illnesses as a part of intervention in their clinical work.
A research report submitted in fulfillment of the requirements for the Master of Arts in Social and Psychological Research , In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Models of illnesses; mental disorder; ANOVA; trainee psychologists; theoretical orientation; assumptions; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth